2021
DOI: 10.29219/fnr.v65.7828
|View full text |Cite
|
Sign up to set email alerts
|

The Nordic Nutrition Recommendations 2022 – prioritisation of topics for de novo systematic reviews

Abstract: Background: As part of the process of updating national dietary reference values (DRVs) and food-based dietary guidelines (FBDGs), the Nordic Nutrition Recommendations 2022 project (NNR2022) will select a limited number of topics for systematic reviews (SRs). Objective: To develop and transparently describe the results of a procedure for prioritisation of topics that may be submitted for SRs in the NNR2022 project. Design: In an open call, scientists, health professionals, national food and health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
54
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 42 publications
0
54
0
Order By: Relevance
“…The group Spreads includes only spreads on bread. 5 Sugar-sweetened beverages. 6 Artificially sweetened beverages.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The group Spreads includes only spreads on bread. 5 Sugar-sweetened beverages. 6 Artificially sweetened beverages.…”
Section: Discussionmentioning
confidence: 99%
“…The DRVs are intended for the general population, considering different age groups and pregnant and lactating women. The framework for the development of the 6th edition (NNR 2022) of the NNR (1) has been described in four articles so far (2)(3)(4)(5).…”
Section: Popular Scientific Summarymentioning
confidence: 99%
See 1 more Smart Citation
“…Criteria for shortlisting topics were published in 2020 ( 10 ). Briefly, it was deemed justified to perform a new systematic review if there were important new scientific data since NNR 2012 or substantial health concerns for Nordic or Baltic countries, and no recent, relevant and qualified systematic review was available on the topic ( 11 ). A scoping review by the NNR Committee identified new data since 2011 that were considered to have the potential to change the dietary reference values or food-based dietary guidance related to protein intake or animal versus plant-based protein in relation to growth and overweight in children.…”
Section: Popular Scientific Summarymentioning
confidence: 99%
“…In updating the 2012 Nordic Nutrition Recommendations (NNR), the role of fat quality in the pathogenesis of AD and related dementias was one of the prioritized topics among the systematic reviews commissioned by NNR Committee. The criteria for prioritization of topics were published a priori ( 18 , 19 ), which indicated that a new systematic review was warranted when important new scientific data have been published on a topic since the NNR 2012. Furthermore, a topic was prioritized in the case that no recent qualified systematic review exists on that topic and if the topic is of substantial health concern for Nordic or Baltic countries.…”
Section: Popular Scientific Summarymentioning
confidence: 99%